Mitologi Nasionalisme dalam Foto Jurnalistik (Analisis Semiotika Roland Barthes) - Munib, Abd (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This scientific work aims to reveal the myth of nationalism in the style of STM students in photojournalism in reflection on the KPK Bill. This journalistic photo is the work of Kompas.com photographer, Garry Andre Lotulung, of STM students carrying red and white flags during a demonstration against the KPK Bill on 25 September 2019 at the DPR building. To interpret the myth of nationalism, the author goes through stages of interpreting the existing symbols. This research uses an interpretive descriptive approach using semiotic analysis methods as a tool used to examine symbols. The data analysis technique used in this research uses Roland Barthes' semiotic analysis. The existence of myth is a distinguishing characteristic that is not found in other semiotic figure models. In order to show the accuracy of the interpretation, it is necessary to interpret the meaning of the first significance and the second significance. Through a series of stages of meaning, a new meaning is found, namely nationalism. The results of this research show that this journalistic photo with all the existing sequences found a hidden meaning in the meaning of the myth of nationalism, namely, the red and white flag carried by STM children to save Indonesia. Karya ilmiah ini bertujuan untuk mengungkap mitos nasionalisme ala pelajar STM pada foto jurnalistik dalam demonstrasi RUU KPK. Foto jurnalistik tersebut merupakan karya fotografer Kompas.com, Garry Andre Lotulung tentang pelajar STM yang membawa bendera merah putih disaat aksi demontrasi penolakan RUU KPK pada 25 September 2019 di gedung DPR. Untuk menginterpretasi mitos nasionalisme itu, penulis melakukan tahapan-tahapan pemaknaan pada simbol-simbol yang ada. Penelitian ini menggunakan pendekatan diskriptif interpretatif dengan menggunakan metode analisis semiotika sebagai alat yang digunakan untuk meneliti simbol-simbol. Teknik analisis data yang digunakan dalam penelitian ini menggunakan analisis semiotika Roland Barthes. Adanya mitos sebagai merupakan ciri pembeda yang tidak dijumpai dalam model tokoh semiotik lainnya. Guna menunjukkan akurasi interpretasi maka perlu dilakukan pemaknaan signifikansi pertama dan signifikansi kedua. Melalui rentetan dari tahapan pemaknaan tersebut ditemukan makna baru yakni nasionalisme. Hasil penelitian ini menunjukkan foto jurnalistik ini dengan segala rangkaian yang ada ditemukan makna tersembunyi makna mitos nasionalisme yakni, bendera merah putih dibawa oleh anak STM untuk menyelamatkan Indonesia